Chemical resolution in T2-T1 correlations - Mitchell, Jonathan; Chandrasekera, Thusara C.; Fordham, Edmund J.; Crawshaw, John; Staniland, John; Johns, Mike L.; Gladden, Lynn F. (Diffusion Fundamentals, 2009)
Oil and water fractions have been identified in fluid saturated carbonate rock cores using a novel T2-T1-d pulse sequence. The inclusion of the chemical shift dimension d allows T2-T1 plots to be generated independently for the oil and water. The T2-T1-d pulse sequence utilises a “double-shot” T1 measurement that provides free induction decays (FIDs) as a function of both relaxation times for suitably broad line samples. The T2-T1-d data set is acquired in the same experimental time as a conventional T1-T2 measurement (without chemical resolution) of equivalent data density. Here we demonstrate that different behaviour can be observed between the oil and water fractions in water wet and preferentially oil wet cores, and that saturation states can be determined. This technique could provide a quantitative NMR measure of wettability.